Challenges of Bitcoin Blockchain Technology in Real-World Apps - Fauzi, Rizky Amien; Nugroho, Indrawan; Saputro, Janu Ilham; Mahesa, Dimas; Fadhillah, Muhammad Daffa (Blockchain Frontier Technology, 2023)
Blockchain is the newest innovation in the fields of internet of things, social media, and cloud computing. Blockchain has quickly become a force to be reckoned with thanks to its reputable uses and rapid development. However, the application of blockchain is not just restricted to bitcoin or other cryptocurrencies. This paper clarifies blockchain requirements outside of bitcoin. In addition, this study offers insights into the mechanics, problems, and evolution of blockchain technology based on a literature review. The difficulties or difficulties in applying blockchain technology to real-world applications were identified in this study. The main issue that needs to be solved is how to securely utilize blockchain technology on small-scale applications.For the secure deployment of the blockchain on small-scale applications or projects, the proposed consensus mechanism might be helpful.